2019
DOI: 10.11604/pamj.2019.33.106.16975
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the uptake of cervical cancer screening among women aged 25-65 years in Kumbo West Health District, Cameroon

Abstract: Introduction Cervical cancer remains one of the leading health hazards affecting a majority women across the globe. The situation is even more, preoccupying particularly in areas where screening programmes and services are absent. The World Health Organization (WHO) says “cervical cancer is the fourth most frequent cancer in women, with an estimated 570,000 new cases diagnosed in 2018 which represents 6.6% of all female cancers. Approximately 90% of deaths from cervical cancer occurred in low- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 14 publications
2
34
1
2
Order By: Relevance
“…In 2018, 2,356 new cases of cervical cancer were diagnosed in women, which represented 14% of all cancers diagnosed in the country, and 25% of cancers diagnosed in women [ 9 ]. Despite this, the uptake of cervical cancer screening among women in Cameroon is less than 20% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, 2,356 new cases of cervical cancer were diagnosed in women, which represented 14% of all cancers diagnosed in the country, and 25% of cancers diagnosed in women [ 9 ]. Despite this, the uptake of cervical cancer screening among women in Cameroon is less than 20% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These included, for example, socioecological barriers associated with interpersonal, social, community and structural factors [ 11 ]. Other factors that limit women’s access to screening included inadequate information and access to existing screening options, the prohibitive cost of accessing existing services, poor health-seeking behaviors, stigma, poorly equipped health infrastructure, and other socio-cultural factors [ 10 ]. The success of cervical cancer prevention in Cameroon will depend on identifying effective strategies to eliminate these contextual challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The major reasons mentioned for not being screened in this study were lack of awareness about the screening (27.1%), has no sign to worry (22%), fear of positive result (15.7%), fear of painful procedure (14.1%), believe they don't have a disease (10.2%). Similarly, a study conducted in Cameron revealed, majority of the respondents (25.3%) mentioned lack of awareness as a reason for not being screened while, 5.53% believed that they were healthy and saw no need for screening and 4.35% thought it could be painful (22). A study conducted in Nigeria also mentioned lack of awareness as the major reason (23).…”
Section: Discussionmentioning
confidence: 97%
“…In 2018, 2, 356 new cases of cervical-cancer were diagnosed in women, which represented 14% of all cancers diagnosed in the country and 25% of cancers diagnosed in women in 2018 (7). Despite this, the uptake of cervical-cancer screening among women in Cameroon is less than 20% (8).…”
Section: Introductionmentioning
confidence: 99%